2021
DOI: 10.3390/ijerph18115945
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in Periodontal Disease According to Insurance Schemes in Thailand

Abstract: Few studies have considered the effects of insurance on periodontal disease. We aimed to investigate the association between insurance schemes and periodontal disease among adults, using Thailand’s National Oral Health Survey (2017) data. A modified Community Periodontal Index was used to measure periodontal disease. Insurance schemes were categorized into the Universal Coverage Scheme (UCS), Civil Servant Medical Benefit Scheme (CSMBS), Social Security Scheme (SSS), and “others”. Poisson regression was applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Our participants were older rural-dwellers who mostly live at a distance from medical services. Most only received basic dental care such as scaling and tooth extraction due to the limited coverage provided by the UCS [ 9 ]. We have provided further evidence of the association between number of teeth lost, cognitive impairment and fall risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our participants were older rural-dwellers who mostly live at a distance from medical services. Most only received basic dental care such as scaling and tooth extraction due to the limited coverage provided by the UCS [ 9 ]. We have provided further evidence of the association between number of teeth lost, cognitive impairment and fall risk.…”
Section: Discussionmentioning
confidence: 99%
“…Thailand’s universal coverage healthcare system is divided into three programs—a civil servant medical benefit scheme (CSMBS) covering 7% of the population, a social security scheme (SSS) for formal-sector private employees covering 15%, and a universal coverage scheme (UCS) for all other Thai citizens that covers about 76% of the population [ 8 ]. According to a recent study by Srinarupat and colleagues, low-income Thai people living in rural areas have a higher prevalence of gingivitis and periodontitis, but face the problem that the service charges for endodontic treatments and surgical removal of posterior teeth are not covered by the UCS [ 9 ]. Periodontitis is the major cause of tooth loss and affects masticatory functions and quality of life [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a systemic review found those in disadvantaged socio-economic status were more susceptible to PD because they had less access to dental care [ 32 ]. Several studies have already shown the necessity and social value of covering dental care benefits in healthcare insurance schemes [ 33 36 ]. Significantly, our findings provide new insight into this issue as well.…”
Section: Discussionmentioning
confidence: 99%
“…The harsh conditions of social development are further affected by challenging barriers to accessing public healthcare and social security [90][91][92]. Regrettably, this situation is prevalent worldwide [93], and scant literature has considered the joint effects of social development on periodontal disease [94].…”
Section: General Findingsmentioning
confidence: 99%